2015
DOI: 10.1097/mot.0000000000000155
|View full text |Cite
|
Sign up to set email alerts
|

Chronic allograft rejection

Abstract: Purpose of review New developments suggest that the graft itself, and molecules expressed within the graft microenvironment dictate the phenotype and evolution of chronic rejection. Recent findings Once ischemia-reperfusion injury, cellular and humoral immune responses target the microvasculature, the associated local tissue hypoxia results in HIF-1α-dependent expression of pro-inflammatory and pro-angiogenic growth factors including vascular endothelial growth factor (VEGF) as a physiological response to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…Furthermore, an increasing body of evidence indicates that the response of the microvasculature to injury ( e.g. activation, protection and/or repair vs. dysfunctional angiogenesis) is critical in both the initiation as well as the progression of chronic rejection [4,5,8,10]. EC injury also results in cell death and microvascular loss, which in turn results in impaired delivery of oxygen and nutrients within the graft parenchyma/tissue.…”
Section: Role Of the Microvasculature In Shaping The Intragraft Micromentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an increasing body of evidence indicates that the response of the microvasculature to injury ( e.g. activation, protection and/or repair vs. dysfunctional angiogenesis) is critical in both the initiation as well as the progression of chronic rejection [4,5,8,10]. EC injury also results in cell death and microvascular loss, which in turn results in impaired delivery of oxygen and nutrients within the graft parenchyma/tissue.…”
Section: Role Of the Microvasculature In Shaping The Intragraft Micromentioning
confidence: 99%
“…Unexpectedly, it was reported that the leukocyte-induced angiogenesis reaction that occurs at early times in the rejection process is associated with local hypoxia [5,7,10], likely due to sluggish and chaotic blood flow patterns, as observed in tumors [4,6,12,26,27]. This is most suggestive that dynamic changes within the EC of an allograft (destruction and/or proliferation) have potential to create abnormal microvascular networks and local areas of tissue hypoxia.…”
Section: Role Of the Microvasculature In Shaping The Intragraft Micromentioning
confidence: 99%
“…Wedel et al (2015) presented new look on the molecular events within the intragraft microenvironment that defines the phenotype of rejection and sustains chronic rejection process. They propose that damage of endothelial cells resulting from ischemia reperfusion injury, T cell cytotoxicity, and alloantibodies.…”
Section: Chronic Allograft Rejectionmentioning
confidence: 99%
“…In models of acute rejection, antibodies to VEGF prolong graft survival. The investigators indicated that new molecules regulated by HIF-1α dependent path, semaphorins, and neurophilins, as well as mTOR/Akt signaling can drive the chronic rejection process (Wedel et al 2015). …”
Section: Chronic Allograft Rejectionmentioning
confidence: 99%
“…In contrast, chronic rejection is still a clinical challenge that limits the long-term survival of transplanted organs [2]. A major pathogenic mechanism underlying chronic rejection is the development of arterial transplant vasculopathy [25].…”
Section: Introductionmentioning
confidence: 99%